From menstrual cycle to pregnancy and motherhood: the tough path to be a female athlete - Di Gioia, G.; Vespasiano, F.; Celeski, M.; Luvero, D.; Crispino, S. P.; Mango, F.; Buzzelli, L.; Segreti, A.; Angioli, R.; Ussia, G. P.; Grigioni, F.; Squeo, M. R. (Sport Sciences for Health, 2025)
Recently, more and more female athletes (FA) have been involved in competitive sports, leading to concerns about the effects of intense physical activity on women`s health. Various types of menstrual irregularities have been described in FA: primary and secondary amenorrhea, oligomenorrhea, short luteal phases, and anovulation. The link between exercise and menstrual irregularities is multifactorial: energy expenditure/availability disbalance and psychological stress associated with training can disrupt the hormonal balance necessary for regular menstruation. Moreover, there is limited research investigating the influence of high-impact exercise on women at different stages of life, especially during pregnancy. In addition, guidelines for pregnant athletes engaging in high-intensity workouts are lacking. Consequently, decisions in such situations are often based on expert advice rather than concrete empirical data, leaving athletes in a state of uncertainty and concern, making it still difficult to adopt new roles such as that of a mother-athlete. This comprehensive narrative review examines the interaction between sports activity and menstrual disorders, pregnancy and postpartum phases, highlighting crucial aspects of women`s health and emphasizing the need for targeted interventions and further research to optimize the well-being of FA.